Development of GeoGebra Interactive Learning Media in Spatial Ability to Build Flat Side Spaces of Cubes dan Beams at SMPN 1 Sunggal - Yasifati Hia; Erika Kristina Br. Nainggolan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the validity, practicality, and effectiveness of GeoGebra-based learning media on the cube and cuboid data side building material that was developed. This research is a research development or Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were 27 students of class IX-3 SMP Negeri 1 Sunggal and the object in this study was an interactive learning media that was developed based on GeoGebra on the material of building blocks and cubes. The data collection technique used a questionnaire sheet for the assessment of material experts, media experts, teacher and student practitioners, as well as learning outcomes tests. The results showed that the GeoGebra-based interactive learning media on the flat side of blocks and cubes obtained an average percentage of 91.31% with